2013
DOI: 10.1104/pp.113.214346
|View full text |Cite
|
Sign up to set email alerts
|

Veratrole Biosynthesis in White Campion    

Abstract: White campion (Silene latifolia) is a dioecious plant that emits 1,2-dimethoxybenzene (veratrole), a potent pollinator attractant to the nocturnal moth Hadena bicruris. Little is known about veratrole biosynthesis, although methylation of 2-methoxyphenol (guaiacol), another volatile emitted from white campion flowers, has been proposed. Here, we explore the biosynthetic route to veratrole. Feeding white campion flowers with [ 13 C 9 ]L-phenylalanine increased guaiacol and veratrole emission, and a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…O ‐methyltransferases were shown to be responsible for the synthesis of a diverse array of benzenoids/phenylpropanoids, including veratrole in Silene flowers (Gupta et al . ; Akhtar & Pichersky ), 3,5‐dimethoxytoluene and 1,3,5‐trimethoxybenzene in roses (Lavid et al . ; Scalliet et al .…”
Section: Biosynthetic Pathways and Genes Involved In The Formation Ofmentioning
confidence: 99%
“…O ‐methyltransferases were shown to be responsible for the synthesis of a diverse array of benzenoids/phenylpropanoids, including veratrole in Silene flowers (Gupta et al . ; Akhtar & Pichersky ), 3,5‐dimethoxytoluene and 1,3,5‐trimethoxybenzene in roses (Lavid et al . ; Scalliet et al .…”
Section: Biosynthetic Pathways and Genes Involved In The Formation Ofmentioning
confidence: 99%
“…These compounds are known to act as pollinator attractants in a number of species . Although their biosynthesis is not well studied, some reports suggest that they are products of the phenylpropanoid biosynthetic pathway . In P. nudicaule , this route is active during the production of pelargonidin, thus suggesting a second biochemical connection between floral volatiles and pigments in the flowers of this species.…”
Section: Resultsmentioning
confidence: 98%
“…A previous study showed that 1,2-dimethoxybenzene (veratrole) is a potent pollinator attractant to the nocturnal moth Hadena bicruris emited by white campion (Silene latifolia: a dioecious plant). Akhtar et al [44] explored firstly the biosynthetic route to veratrole. Then, suggested that it was derived by the methylation of guaiacol (2-methoxyphenol), which itself originates from phenylalanine via BA (benzoic acid) and SA (salicylic acid), and therefore implies a novel branch point of the general phenylpropanoid pathway.…”
Section: Resultsmentioning
confidence: 99%